Extent of patients’ satisfaction in the external services department of Al-Iman General Hospital - Almotairi, Faris Wazin; Sumaida, Omar Ali Al-Sagheer (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the extent of patient satisfaction in the external services section of the General Eman Hospital, and the problem of the study is summarized in the following question, which is the extent of the patients ’satisfaction in the external services section of the general faith hospital from the viewpoint of auditors of the general faith hospital in Riyadh, and the study has significance as the study is a step to identify On the level of quality of medical services aimed at patient satisfaction in the External Services Department of Al-Iman General Hospital. Likewise, this study came to know the level of quality of services provided to patients in the external services department of Al-Iman General Hospital in order to put it and put officials in the picture of the matter, and the study identified hypotheses and there are no statistically significant differences at the level of significance (5 = 0.05) towards the level of patient satisfaction, and the quality Actual services in the External Services Department of Al-Iman General Hospital, depending on gender, age and educational qualification. The descriptive analytical approach was used to achieve the goals of the study, and the questionnaire was used as a tool to collect data, and the study community consisted of auditors of Al Iman General Hospital in Riyadh, and the study sample consisted of (110) male and female auditors from Al Iman Hospital, and a set of statistical methods were used to process the study data By using the SPSS program. In light of this, a number of results were reached, the most important of which are: Health care services, such as the dimensions of service quality, tangibility: (tangible physical aspects), response, safety, and sympathy for patients, to satisfy patients in the external services department of Iman Hospital, have a significant and positive impact on patient satisfaction. Likewise, the degree of satisfaction was satisfactory with regard to the dimensions of quality of service, tangibility: (tangible physical aspects), response, safety, and sympathy for patients, to satisfy patients in the external services department of Iman Hospital. In light of the results, the study recommends the following: - Doctors and nurses should pay attention to the auditors, pay attention to the problems and inquiries of patients, and urge to provide services on time without delay, to meet the requests of patients immediately. - The hospital administration should work on everything that improves the level of satisfaction of the auditors with the provision of modern devices that contribute to providing good medical services, attention to the problems and inquiries of patients, attention to the cleanliness of hospital facilities and the development of medical guidelines, and provide waiting places for auditors.